PREVENTION OF SUDDEN CARDIAC DEATH IN ATHLETES WITH ARRHYTHMIAS – CURRENT GUIDELINES AND CONTROVERSIES - Karol Szyprowski; Agata Trześniowska; Kinga Szymańska; Alicja Weronika Ściseł; Wiktoria Konaszczuk (International Journal of Innovative Technologies in Social Science, 2025)
Purpose: This paper aims to conduct a thorough examination of contemporary studies pertaining to the prophylaxis of unexpected cardiac mortality in athletes presenting with arrhythmic conditions. Methodology: A thorough and extensive literature review was undertaken utilizing various scientific databases, such as PubMed, Scopus, and Google Scholar. The criteria for selection emphasized clinical trials, systematic reviews, and meta-analyses that examined sudden cardiac death in athletic populations. The studies were assessed for their methodological robustness, relevance, and practical implications, with particular focus on the risk determinants and essential recommendations. Findings: Early detection and risk stratification are key to preventing SCD in athletes. Individualized preventive strategies, including lifestyle changes, medical therapy, and ICDs, should be led by a multidisciplinary team. Genetic testing can aid in identifying inherited conditions but is mostly limited to specialist centers. Ongoing disparities in access highlight the need for coordinated international action. Conclusions: Preventing SCD in athletes requires personalized, team-based care and improved access to diagnostics. Wider implementation of genetic testing and harmonized global guidelines are essential to address current gaps and ensure effective prevention.